2021
DOI: 10.3390/pharmaceutics13122080
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Surface Drug Distribution on the Acoustic Behavior of DOX-Loaded Microbubbles

Abstract: Previous studies have reported substantial improvement of microbubble (MB)-mediated drug delivery with ultrasound when drugs are loaded onto the MB shell compared with a physical mixture. However, drug loading may affect shell properties that determine the acoustic responsiveness of MBs, producing unpredictable outcomes. The aim of this study is to reveal how the surface loaded drug (doxorubicin, DOX) affects the acoustic properties of MBs. A suitable formulation of MBs for DOX loading was first identified by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…The improvement of blood perfusion signals at the peripheral microcirculation of ACArb after OMB treatment was visualized in the laser speckle images (Figure S4). Since MB cavitation can activate release of the vasodilator nitric oxide (NO), sonoperfusion might promote effective reperfusion in the microcirculation to protect neurons [18,22]. In addition, the local release of O 2 during OMB treatment promoted a 10.3 ± 3.1% increase in pO 2 level relative to the S/R group, allowing reoxygenation of the hypoxic brain.…”
Section: Discussionmentioning
confidence: 99%
“…The improvement of blood perfusion signals at the peripheral microcirculation of ACArb after OMB treatment was visualized in the laser speckle images (Figure S4). Since MB cavitation can activate release of the vasodilator nitric oxide (NO), sonoperfusion might promote effective reperfusion in the microcirculation to protect neurons [18,22]. In addition, the local release of O 2 during OMB treatment promoted a 10.3 ± 3.1% increase in pO 2 level relative to the S/R group, allowing reoxygenation of the hypoxic brain.…”
Section: Discussionmentioning
confidence: 99%
“…This study employed the thin film hydration method to synthesize MBs following previous publication [2] , using three types of lipids: 1,2-distearoyl- sn -glycero-3-phosphocholine (DSPC, Avanti Polar Lipids, AL, USA), 1,2-distearoyl- sn -glycero-3-phospho- rac -glycerol sodium salt (DSPG, Avanti Polar Lipids, AL, USA), and 1,2-distearoyl- sn -glycero-3-phosphoethanolamine-N-[methoxy(poly(ethylene glycol))-2000] (DSPE-PEG2000, Avanti Polar Lipids, AL, USA). DSPC, DSPG, and DSPE-PEG2000 were dissolved in chloroform with a mole ratio of 42:63:2.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, cavitation serves as a trigger for the controlled release of drug payloads from these microbubbles in response to US sonication. It is essential to acknowledge that most reported studies have indicated that the composition of the payload significantly influences the acoustic properties of drug-loaded MBs onto the shell of the MBs [1] , [2] . Leveraging these distinctive acoustic properties and drug release behaviors associated with drug-loaded MBs containing various types of surface drug distribution holds the potential to enable precise control over their behavior, thus expanding their utility in the realm of medical applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 101 Moreover, US microvesicles can also be used as gene and drug delivery carriers, providing a dual advantage in the diagnosis and treatment of tumors. Lin et al 102 found that new DOX-loaded MBs could be safely applied in rats, resulting in a corresponding increase in the local drug concentration and inhibition of tumor growth. In clinical case studies of patients with locally advanced and inoperable pancreatic cancer, it was found that the combination of US, MBs and chemotherapy significantly increased the treatment cycle and extended the quality of life of patients with pancreatic adenocarcinoma compared with chemotherapy alone.…”
Section: Microbubble-assisted Us For Drug Delivery Purposesmentioning
confidence: 99%